Targeting SOX2 as a Therapeutic Strategy in Glioblastoma - Garros-Regulez, Laura; Garcia, Idoia; Carrasco-Garcia, Estefania; Lantero, Aquilino; Aldaz, Paula; Moreno-Cugnon, Leire; Arrizabalaga, Olatz; Undabeitia, Jose; Torres-Bayona, Sergio; Villanua, Jorge; Ruiz, Irune; Egaña, Larraitz; et al. (Frontiers in Oncology, 2016)
Glioblastoma is the most common and malignant brain cancer in adults. Current therapy consisting of surgery followed by radiation and temozolomide therapy has moderate success rate and the tumor reappears. Among the features that a cancer cell must have to survive the therapeutic treatment and reconstitute the tumor is the ability to self-renewal. Therefore, it is vital to identify the molecular mechanisms that regulate this activity. SOX2 is a transcription factor whose activity has been associated with the maintenance of the undifferentiated state of cancer stem cells in several tissues including the brain. Several groups have detected SOX2 levels increased in biopsies of glioblastoma patients, with highest levels associated to poor outcome. Therefore, SOX2 silencing might be a novel therapeutic approach to combat cancer and particularly brain tumors.In this review, we will summarize the current knowledge about SOX2 in glioblastoma and recapitulate several strategies, which have been recently described targeting SOX2 in this malignancy.